BAHASA INDONESIA RAGAM TULIS DI KALANGAN SISWA REMAJADI DKI JAKARTA - Wati Kurniawati (Kandai, 2017)
This study aimed to describe the quality of Indonesian variety of writing used by high school students in Central Jakarta and East Jakarta. The focus of this research is the spelling rules. The method used is descriptive method. Fourty high school students writing in Central Jakarta and East Jakarta were selected as the sample, they are consisting of twenty men and twenty women with regard to social factors. The findings indicate that female teenage student, female students in Central Jakarta more careful in the use of the letters, punctuation, and spelling than male teenage student in East Jakarta. Students whose parents are having different ethnic tend to be more careful in the use of letters and writing words than students whose parents is coming from same ethnic. As for the use of punctuation on students whose parents is coming from same ethnic tend to be more careful than teenage student whose parents are having different ethnic.